2014
DOI: 10.1080/09593330.2014.902110
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of struvite via coagulation and flocculation using natural compounds

Abstract: One of the major setbacks of struvite recovery processes is the difficulty in harvesting struvite crystals. This study evaluates the use of different coagulants to improve precipitation of struvite (MgNH4PO4.6H20) crystals. Chitosan and poly(diallyldimethyl ammonium chloride) (Poly-DADMAC) as a coagulant-flocculent and alginate and bentonite as a coagulant aid have been examined in jar tests. Also, a continuous three-phase process, i.e., struvite crystallization, coagulation/flocculation and precipitation proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…By comparison, there are sparse reports where chitosan is used for the removal of particulate matter and dissolved substances in homogeneous solution. Chitosan has unique properties as a coagulant and/or flocculant due to its pH-dependent charge density and variable molecular weight, along with its chelation and aggregation behavior at pH conditions above its p K a value . The unique physicochemical properties of chitosan along with biodegradability, biocompatibility, metal chelation, and low toxicity favor its use as a biopolymer flocculant. , Chitosan has been used for the removal of P i in wastewater using different techniques or processes besides coagulation and flocculation. Teh and Wu have also shown that the amount of sludge produced using chitosan was significantly lesser as compared to alum…”
Section: Introductionmentioning
confidence: 99%
“…By comparison, there are sparse reports where chitosan is used for the removal of particulate matter and dissolved substances in homogeneous solution. Chitosan has unique properties as a coagulant and/or flocculant due to its pH-dependent charge density and variable molecular weight, along with its chelation and aggregation behavior at pH conditions above its p K a value . The unique physicochemical properties of chitosan along with biodegradability, biocompatibility, metal chelation, and low toxicity favor its use as a biopolymer flocculant. , Chitosan has been used for the removal of P i in wastewater using different techniques or processes besides coagulation and flocculation. Teh and Wu have also shown that the amount of sludge produced using chitosan was significantly lesser as compared to alum…”
Section: Introductionmentioning
confidence: 99%
“…Latifian et al (2014) measured at 7.4 cm deep an average settling velocity of 14 cm.min −1 in synthetic wastewater and of 8 cm.min −1 in real wastewater. Average velocities greater than 14 cm.min −1 are here measured for depths below 0.74 and 0.34 m in the 45 and 90 ppm solutions, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have been conducted about flocculant addition on struvite recovery: Le Corre et al (2007) evaluated the agglomerative property of different coagulant/flocculant over struvite and identified polyDADMAC as a good option; Etter et al (2011) investigated the potential of Moringa Oleifera , as flocculants on struvite, but no improvement in terms of settling rates were shown; and Latifian et al (2014) studied different coagulant/flocculant (chitosan and polyDADMAC) and coagulant aid (bentonite and sodium alginate). Chitosan–bentonite used as the coagulant and coagulant aid significantly increased the average settling velocity of struvite crystals; however, smaller flocs formed in the continuous system (compared with jar tests).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations